PV generator-fed water pumping system based on a SRM with a multilevel fault-tolerant converter - Fernao Pires, Vitor (2022)
This paper presents a pumping system supplied by a PV generator that is based on a switched reluctance machine (SRM). Water pumping systems are fundamental in many applications. Most of them can be used only during the day; therefore, they are highly recommended for use with PV generators. For the interface between the PV panels and the motor, a new multilevel converter is proposed. This converter is designed in order to ensure fault-tolerant capability for open switch faults. The converter is based on two three-level inverters, with some extra switches. Moreover, to reduce the number of switches, the converter is designed to provide inverse currents in the motor windings. Due to the characteristics of this motor, the inverse currents do not change the torque direction. In this way, it was possible to obtain an SRM drive with fault-tolerant capability for transistor faults; it is also a low-cost solution, due to the reduced number of switches and drives. These characteristics of fault-tolerant capability and low cost are important in applications such as water pumping systems supplied by PV generators. The proposed system was verified by several tests that were carried out by a simulation program. The experimental results, obtained from a laboratory prototype, are also presented, with the purpose of validating the simulation tests.